STRATEGI ISLAMIC GREEN EDUCATION DALAM MEMBANGUN KESADARAN EKOTEOLOGI MELALUI STUDI PEMBELAJARAN AGAMA ISLAM SEBAGAI GREEN DESIGN EKONOMI HIJAU - Febrianto Hakeu; Ridwanto Djahuno; Adelia Akuba; Avelya Deysi Ramadya (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the strategy of Islamic Green Education in building ecological awareness through learning Islamic religion as a green design of the green economy in the madrasah environment. The background of this research departs from the low integration of ecotheology values in PAI learning which tends to focus on the cognitive realm, so that students' ecological awareness has not been formed optimally. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The data obtained were analyzed descriptively to explore the extent of the application of ecotheological values in the learning process of Islam. The results of the study show that the implementation of Islamic Green Education in PAI learning is still limited and has not been systematically structured. The main influencing factors are the lack of integration of ecotheological values in the curriculum, the limited creativity of teachers in linking Islamic teachings with environmental issues, and the lack of institutional support. However, it was found that students were more enthusiastic and easily understood Islamic teachings when associated with the practice of maintaining the daily environment. Therefore, a solution strategy is needed in the form of developing an ecotheology-based curriculum, improving teacher competence, and forming a green madrasah ecosystem that involves the community.